2019
DOI: 10.1084/jem.20190832
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase Nsd2 is required for follicular helper T cell differentiation

Abstract: Follicular helper T (Tfh) cells provide essential help for humoral immune response. Transcriptional factor Bcl6 is the master regulator for Tfh generation and is induced very early after T cell activation in a CD28-dependent manner, but how CD28 signal promotes Bcl6 early expression remains unknown. Here we found that CD28 signal quickly induces expression of the H3K36me2 methytransferase Nsd2, which is required for Bcl6 expression as early as the first cell division after T cell activation. Nsd2 deficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Bcl6 expression is induced by IL-6-STAT1/STAT3 signaling [43], and it is driven very early after T cell activation in a CD28-dependent manner [44]. The E3 ubiquitin ligase Itch is essential for Bcl6 expression at the early stage of Tfh cell development [45].…”
Section: Bcl6 and Blimp-1mentioning
confidence: 99%
“…Bcl6 expression is induced by IL-6-STAT1/STAT3 signaling [43], and it is driven very early after T cell activation in a CD28-dependent manner [44]. The E3 ubiquitin ligase Itch is essential for Bcl6 expression at the early stage of Tfh cell development [45].…”
Section: Bcl6 and Blimp-1mentioning
confidence: 99%
“…Deubiquitination of histones and DNA methylation in T cells can promote their expansion (Dufner et al, 2015;Lee et al, 2001;Manna et al, 2015). Histone acetylation and methylation have also been reported to positively regulate T-cell development (Boucheron et al, 2014;Gao et al, 2017;Gö schl et al, 2018;Long et al, 2020;Philips et al, 2016;Takikita et al, 2016;Toubai et al, 2018). T helper type 1 (Th1) cells are positively driven by citrullination (Liu et al, 2018b) and negatively regulated by DNA demethylation (Carty et al, 2018).…”
Section: T Cellsmentioning
confidence: 99%
“…Histone demethylase KDM6A has shown activity in urothelium (Kobatake et al, 2020), histone methyltransferase G9a in KCs (Li et al, 2018), and SETDB1 in intestinal epithelial cells (Ju zni c et al, 2020). Inflammatory cytokines have been also shown to be positively regulated by HDAC3 in intestinal epithelial cells (Navabi et al, 2017), HDAC5 in bronchial epithelial cells (Luo et al, 2019), and HDAC6 in bronchial epithelial cells (Lin et al, 2020). Histone demethylation enzymes JMJD3 and SET7/9 positively regulate the production of antimicrobial peptides by KCs (Gschwandtner et al, 2014) and inflammatory cytokines by bronchial epithelial cells (He et al, 2015), respectively.…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that deficiency of the H3K36me2 methyltransferase Nsd2 in T cells leads to decreased Bcl‐6 expression and impaired Tfh cell generation. CD28 activation quickly induces the expression of Nsd2 (Long et al, 2020). In addition, the transcription factors BATF (basic leucine zipper ATF‐like transcription factor), IRF4 (interferon regulatory factor 4), TCF‐1, LEF‐1 (lymphoid enhancer‐binding factor 1), and Thpok (T‐helper‐inducing POZ/Krueppel‐like factor) play essential roles in the regulation of Bcl‐6 (Y. S. Choi et al, 2015; Vacchio et al, 2019; Vinuesa et al, 2016).…”
Section: Direct Regulation Of Tfh Cell Differentiation and Functionmentioning
confidence: 99%